Study of information needs of students in the field of environmental policy - I. D. Porfirieva (Управление)
The ecological crisis, which so suddenly stroke the human habitat, made significant adjustments in the relationship between nature and man, forced to reconsider all the significant developments of human civilization and is extremely actualized today social and environmental issues at all levels: regional, national, global. In this regard, the ecological issues, as a result of man’s consumer attitude towards the entire natural system, are today among the most discussed topics in scientific publications, in the media space, and in scientific discourse. The thoughtless, unlimited satisfaction of the growing needs of people has led to an irreversible change in the properties of landscapes, the depletion and loss of minerals, the disappearance of many species of the animal and plant world. Unsolved problems in the field of ecology, at the moment, reflect the reality of the twenty-first century. Solving the environmental problems, that have arisen, depends not so much on the level of development of production, science and technology, but on the ecological culture of the population, on understanding the sources, nature and ways out of the current crisis situation, on everyone’s participation in preserving natural resources, minimizing waste products.In the article, based on the study of the state of environmental consciousness of students, the role of environmental education as a factor in the formation of culture, moral standards in relations with nature, and overcoming the environmental crisis has considered. The data obtained allowed to substantiate the conclusions about the need for fundamental changes in educational programs, toughening legal regulations in the field of environmental management as a mechanism to counter the extinction and death of civilization.